2020
DOI: 10.1002/jsfa.10252
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bioaccessibility and activity of Greek oregano (Origanum vulgare L. ssp. hirtum (link) Ietswaart) compounds as affected by nitrogen fertilization

Abstract: BACKGROUND Greek oregano is a culinary and medicinal herb native to the Mediterranean region; however nowadays it is cultivated in many regions all over the world. It is commonly used as a spice for flavoring food products and in various traditional medicine applications. This study investigated the effect of nitrogen fertilization at 0–150 kg N ha−1 on the potential bioaccessibility and activity of Greek oregano compounds. For this purpose the total phenolic content, rosmarinic acid content, and antioxidant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Furthermore, compared with other valuable natural sources of antioxidants, e.g., Greek oregano, whose extracts and by-products are recognized as strong antioxidant agents for food preservation [74], higher antioxidant activity was determined for bearberry. Previous studies indicate that the antiradical activity in Greek oregano ranged from 150.8 to 235.1 mg TE g −1 against ABTS, from 101.8 to 160.7 mg TE g −1 against DPPH, and from 73.2 to 114.4 TE g −1 of ferric reducing power, depending on cultivation conditions (nitrogen dose), in the case of the same analytical procedures [75]. Figure 12 shows the results of the PCA ordination of the bearberry samples.…”
Section: Antioxidant Activitymentioning
confidence: 97%
“…Furthermore, compared with other valuable natural sources of antioxidants, e.g., Greek oregano, whose extracts and by-products are recognized as strong antioxidant agents for food preservation [74], higher antioxidant activity was determined for bearberry. Previous studies indicate that the antiradical activity in Greek oregano ranged from 150.8 to 235.1 mg TE g −1 against ABTS, from 101.8 to 160.7 mg TE g −1 against DPPH, and from 73.2 to 114.4 TE g −1 of ferric reducing power, depending on cultivation conditions (nitrogen dose), in the case of the same analytical procedures [75]. Figure 12 shows the results of the PCA ordination of the bearberry samples.…”
Section: Antioxidant Activitymentioning
confidence: 97%
“…According to Bueno-Duran [12], different spectra of light affect the monoterpene content; based on this, red light increases the carvacrol content, blue light increases the thymol content in L. graveolens, and UV-C light application increases the total phenolic content [13]. Moreover, nitrogen deficiency enhances secondary metabolites' production, such as phenolic compounds and flavonoids in Greek oregano [14].…”
Section: Introductionmentioning
confidence: 99%
“…family native to the northeast regions of the Mediterranean basin i.e. Greece, the Balkans, Turkey, and Cyprus, 14 Besides the areas of natural occurrence, this plant is cultivated worldwide because of its versatile uses as a culinary, medicinal, aromatic, melliferous, and ornamental herb. 15,16 The main purpose of the use of Greek oregano is to flavor such dishes as soups, salads, sauces, and meats; however, it is also used as a natural preservative to protect against deterioration and prolong the storage time of various foods.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The main purpose of the use of Greek oregano is to flavor such dishes as soups, salads, sauces, and meats; however, it is also used as a natural preservative to protect against deterioration and prolong the storage time of various foods. 14 In traditional phytotherapy, oregano-derived medications have been employed for the prevention and treatment of cold, cough, headache, diabetes, and digestive disorders. 17,18 Furthermore, previous scientific data have shown that this herb is characterized by a wide range of beneficial activities, such as antibacterial, antifungal, antioxidant, anti-inflammatory, antiproliferative, antispasmodic, diaphoretic, sedative, diuretic, tonic, and carminative activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation